Characterisation of guided entry of tail-anchored proteins in Magnaporthe oryzae. - Felix Abah; Qiaojia Zheng; Xinru Chen; Linwan Huang; Xiaomin Chen; Jules Biregeya; Osakina Aron; Zonghua Wang; Wei Tang (PLoS Pathogens)
Rice (Oryza sativa L.) is one of the most important staple foods for human population worldwide. However, rice production continues to be severely threatened by rice blast disease caused by an ascomycete fungus Magnaporthe oryzae. Tail-anchored (TA) proteins are conserved across diverse organisms and belong to a class of polypeptides that are inserted into the membrane by a hydrophobic sequence located at the C-terminal region. The Guided Entry of Tail-anchored (GET) complex is responsible for the post-translational insertion of nascent TA proteins into the Saccharomyces cerevisiae ER lipid bilayer. In S. cerevisiae, the GET pathway comprises six known associated components Get1, Get2, Get3, Get4, Get5, Sgt2 and Ssa1 that have been identified and extensively studied. However, the role of the GET complex in rice blast fungus has not been elucidated. Here, we identified five proteins of the GET Complex in M. oryzae, namely MoGet1, MoGet2, MoGet3, MoGet4 and MoSgt2 and generated the gene knock-out mutants. Deletion of MoGET1 and MoGET2 revealed that they are required for vegetative growth, asexual reproduction, pathogenesis, and right localization of TA protein, MoYsy6, while MoGet3 negatively regulates hyphal growth, asexual development and pathogenesis of M. oryzae. In contrast, loss of MoGet4 and MoSgt2 had no effect on the normal development of the rice blast fungus. We demonstrated that the MoGet2 is important in osmotic stress response and positively regulates cell wall integrity. The MoGet1 and MoGet2 were ER-localized and indispensable for DTT-induced ER stress response. In vitro and in vivo interaction assay revealed MoGet3 has physical interaction with both MoGet1 and MoGet2, indicating the existence of a possible synergistic function amongst the Get components in rice blast fungus. In summary, this finding provides valuable insight into the biological functions of the GET components in plant fungal pathogens.